Led enhance the growth characteristics and affects the ex vitro aclimatization of sugarcane - Pinheiro, Marcos Vinicius Marques; Thiesen, Leonardo Antonio; Massolino, Cristiano; Masarro-Araújo, Guilherme; Diel, Maria Inês; Schmidt, Denise (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2022)
The proper selection and optimization of light and gas-permeable membranes in the culture flasks, can benefit plant quality and improve ex vitro acclimatization capacity. The objective was to compare the morpho-physiological responses of in vitro sugarcane plants in different LEDs and sealing flask types and their impact in ex vitro acclimatization. Plants previously established in vitro were used and inoculated in flasks sealed with rigid caps with or without gas-porous membranes, and maintained in growth room (25 ± 2 ºC, 16 h photoperiod, and 72 μmol m-2s-1 irradiance from LEDs (white, blue/red, blue or red). At 62 days of in vitro cultivation growth and physiological parameters were evaluated. Blue/red LEDs and flasks without gas-porous membranes provided a higher number of shoots and blue LEDs a higher plant height. We observed greater number of leaves per clump in blue/red LED, and length of the largest root in flasks without gas-porous membranes. Red LEDs provided higher shoot fresh mass and the plants under blue and white LEDs had higher root fresh mass, being the same performance observed in shoot and root dry mass. The highest content of chlorophyll a and carotenoids was observed in plants kept in flasks without membranes and blue and red LEDs. The highest percentage of plant acclimatization were cultured under white LEDs (85%), and blue/red LEDs (70%).For this, to produce sugarcane in vitro, we suggest the use of culture flasks whitout membranes and blue/red or white LED lamps, as they provide more hardening plants standing out in excellent acclimatization of cultures. Index terms: Light-emitting diodes; Saccharum officinarum; gas-permeable membranes; natural ventilation.